2020
DOI: 10.1111/ejn.14959
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐motor interference in the wild: Assessing the effects of movement complexity on task switching using mobile EEG

Abstract: Adaptively changing between different tasks while in locomotion is a fundamental prerequisite of modern daily life. The cognitive processes underlying dual tasking have been investigated extensively using EEG. Due to technological restrictions, however, this was not possible for dual-task scenarios including locomotion. With new technological opportunities, this became possible and cognitive-motor interference can be studied, even in outside-the-lab environments. In the present study, par-How to cite this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 78 publications
1
61
1
Order By: Relevance
“…In our case, an average of 23 % of the probes were classified as mind wandering (across groups), which corresponds to an average of 9 mind wandering epochs per participant. In order to overcome this limitation, future studies could perform multiple (mobile) EEG recording sessions in the same subjects (Reiser et al, 2020) thereby allowing the identification of a greater number and variety of mind wandering periods.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, an average of 23 % of the probes were classified as mind wandering (across groups), which corresponds to an average of 9 mind wandering epochs per participant. In order to overcome this limitation, future studies could perform multiple (mobile) EEG recording sessions in the same subjects (Reiser et al, 2020) thereby allowing the identification of a greater number and variety of mind wandering periods.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring MWL in a multimodal manner seems to be an appropriate solution for this problem [18,[30][31][32]. Methods for MWL assessment can be categorized in subjective, performance based, and physiological measurements with an increasing tendency for wearable, mobile, and non-invasive neurophysiological methods like eye-tracking, EEG, or fNIRS [33][34][35]. Compared to performance based data and subjective ratings, physiological methods offer a continuous data stream and thus offer chances for live analysis using machine learning algorithms and a direct approach to identify task related changes in MWL (for example, using heart rate (HR), see [36]).…”
Section: Mental Workload and The Problem Of Robust Quantificationmentioning
confidence: 99%
“…With amplifiers becoming much smaller and more mobile than just some years ago, study designs were enabled that allowed participants to move in full-body motion, either in laboratory facilities (Gramann et al, 2010;Shaw et al, 2018) or in real-life environments (Ladouce et al, 2016(Ladouce et al, , 2019Reiser et al, 2019Reiser et al, , 2020Scanlon et al, 2019). Studying the influence of real-world motion on cognitive processes, these studies found that even locomotion impairs the availability of cognitive resources.…”
Section: Measures In the Time Domain: Event-related Potentialsmentioning
confidence: 99%
“…Furthermore, frontal midline Theta was found to be modulated by task load, multitasking, and prolonged focused attention in several basic research and workplace simulation tasks (for an overview, see Borghini et al, 2014). In mobile EEG recordings, different patterns of Theta activation were found for experimental conditions in which participants were in motion compared to standing, all while performing a cognitive task (Pizzamiglio et al, 2017;Reiser et al, 2019Reiser et al, , 2020Shaw et al, 2018). These results highlight the role of frontal midline Theta as a correlate of central executive mechanism during locomotion that controls resource allocation in situations of cognitivemotor interference.…”
Section: Measures In the Time Domain: Event-related Potentialsmentioning
confidence: 99%